Film dan Perempuan: Kegagalan Film Gone Girl dalam Membentuk Sosok Perempuan Baru di Industri Film Hollywood - Yusriana, Amida; Zulfiningrum, Rahmawati (Universitas Semarang, 2016)
Gone Girl is a film produced in 2014 and is an adaptation of a best-selling novel by Gillian Flynn. Gone Girl can be divided into three parts. The interesting point in this movie is the gender focus of Gillian Flynn s way in depicting Amy. According to her, this is an attempt to show that woman can have a criminal mind as a man. However, the depiction of woman in patriarch charasteristic is still can be found in the movie. This research is to find out how the movie Gone Girl failed to create a new woman character.This study uses the postmodernism theory to explain. Result of this study indicates that the figure of Amy Dunne is described as a heroine with typical utopia and as a villain Amy can not be separated from the feminines roles of patriarch. Among others: weak, emotional human being, depending and using her body as a weapon.